2011
DOI: 10.1080/0361073x.2011.590757
|View full text |Cite
|
Sign up to set email alerts
|

Age Differences in Daily Predictors of Forgetting to Take Medication: The Importance of Context and Cognition

Abstract: The present study examined age differences in the within-person daily associations of basic cognition, everyday cognition, and busyness with forgetting to take medication. The authors extend previous interindividual difference findings by conducting a daily diary study of a baseline assessment and 8 consecutive days of 40 older adults (age = 60-89 years, M = 74.86) and 31 younger adults (age = 18-20 years, M = 18.30) where basic cognition, everyday cognition, busyness, and forgetting medication were assessed e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…We are not the first investigators to identify older age as a factor in nonadherence 5,15,37. Poor sleep quality is also known to impair the ability to pay attention and make good decisions 38,39.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…We are not the first investigators to identify older age as a factor in nonadherence 5,15,37. Poor sleep quality is also known to impair the ability to pay attention and make good decisions 38,39.…”
Section: Discussionmentioning
confidence: 97%
“…Poor sleep quality is also known to impair the ability to pay attention and make good decisions 38,39. However, the interaction of older age and poor sleep quality may be best explained by the compelling mechanistic explanation described by Neupert et al37 who examined how daily fluctuations in cognition and busyness are related to daily fluctuations in forgetting to take medications and whether these within-person relationships differed for younger and older adults. On days when the older adults in their study were relatively less busy, they were at lower risk for forgetting to take their medicines, but only if they were also performing well on the everyday cognition assessments.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, lab-based research is limited to hours of operation that require alteration of the participant’s daily routine. Previous work has shown that older adults show better performance on memory tasks that are part of a structured routine (Neupert, Patterson, Davis, & Allaire, 2011; Rose, Rendell, McDaniel, Aberle & Kliegel, 2010). Home-based testing as realized in the present study may reduce performance deficits due to these factors.…”
Section: Discussionmentioning
confidence: 99%
“…They have revealed that performance variability in older adults is related to affect, control beliefs, and physiological indicators of arousal [9,10]. For example, Riediger et al [10] found that tense arousal and physiological activation were accompanied by impairments in cognitive performance in middle and later adulthood.…”
Section: Contemporary Use Of Aa In the Research On Agingmentioning
confidence: 99%
“…For example, Riediger et al [10] found that tense arousal and physiological activation were accompanied by impairments in cognitive performance in middle and later adulthood. These findings indicate the importance of restraining oneself from hectic schedules in old age and from engaging in cognitively demanding activities, such as driving in times of stress [9]. …”
Section: Contemporary Use Of Aa In the Research On Agingmentioning
confidence: 99%